2014
DOI: 10.1016/j.ijcard.2014.03.086
|View full text |Cite
|
Sign up to set email alerts
|

15-deoxy-Δ12,14-PGJ2 promotes inflammation and apoptosis in cardiomyocytes via the DP2/MAPK/TNFα axis

Abstract: BackgroundProstaglandins (PGs), lipid autacoids derived from arachidonic acid, play a pivotal role during inflammation. PGD2 synthase is abundantly expressed in heart tissue and PGD2 has recently been found to induce cardiomyocyte apoptosis. PGD2 is an unstable prostanoid metabolite; therefore the objective of the present study was to elucidate whether its final dehydration product, 15-deoxy-Δ12,14-PGJ2 (15d-PGJ2, present at high levels in ischemic myocardium) might cause cardiomyocyte damage.Methods and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 68 publications
1
44
0
1
Order By: Relevance
“…We read with great interest the article by Koyani et al reporting that 15-deoxy-Δ 12,14 -prostaglandin (PG) J 2 (15d-PGJ 2 ) promotes apoptosis and inflammation in cardiomyocytes [1]. Although there is no question that 15d-PGJ 2 and relatives including Δ 12 -PGJ 3 have multiple biological activities [2][3][4][5][6][7][8][9], the most important question is still [10] whether 15d-PGJ 2 is formed in vivo at sufficiently high concentrations or can be applied pharmacologically or nutritionally at such doses that are likely to provide 15d-PGJ 2 concentrations high enough to exert biologic activity.…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…We read with great interest the article by Koyani et al reporting that 15-deoxy-Δ 12,14 -prostaglandin (PG) J 2 (15d-PGJ 2 ) promotes apoptosis and inflammation in cardiomyocytes [1]. Although there is no question that 15d-PGJ 2 and relatives including Δ 12 -PGJ 3 have multiple biological activities [2][3][4][5][6][7][8][9], the most important question is still [10] whether 15d-PGJ 2 is formed in vivo at sufficiently high concentrations or can be applied pharmacologically or nutritionally at such doses that are likely to provide 15d-PGJ 2 concentrations high enough to exert biologic activity.…”
Section: To the Editormentioning
confidence: 99%
“…These values correspond to 15d-PGJ 2 concentrations of 0.4 and 0.7 nM, respectively. Thus, in the study by Koyani et al [1] and in studies from other groups [3][4][5][6][7][8], 15d-PGJ 2 was used in the majority of their experiments at a concentration of 15 μM, which is at least three orders of magnitude higher than expectable tissue 15d-PGJ 2 concentrations. Lower, more pathophysiologically relevant but still too high concentrations (e.g., 50 nM) were used only in very few experiments [1].…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Saba et al25 found that cardiac‐specific overexpression of TNF‐α could cause atrial contractile dysfunction, fibrosis, and arrhythmias in a mouse model. Moreover, a recent study has revealed that enhanced expression of TNF‐α in the murine atrial cardiomyocyte HL‐1 cell line promoted cardiomyocyte apoptosis by activating CASP‐3 26. IL‐6 has also been shown to be an important regulator of cardiac interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%